A New Earthworm Species of the Genus Metaphire Sims & Easton, 1972 (Oligochaeta: Megascolecidae) from Southern Vietnam - Nguyen, Tung Thanh; Ly, Vuong Van; Lam, Dang Hai; Nguyen, Thuan Van; Nguyen, Anh Duc (Tropical Natural History, 2022)
A new species, Metaphire acampanulata sp. nov., was described from Southern Vietnam. The species belonging to Metaphire houlleti species-group, can be characterized by having three pairs of spermathecal pores in 6/7/8/9, genital markings invisible, first dorsal pore in 11/12 or 12/13, spermatheca mushroom-shaped, ampulla duct L-shaped, and penial setae present. The K2P genetic distance based on a 600 bp fragment of the mitochondrial gene, COI, between the new species and its closely related one, M. houlleti, was 18.8%, and the intraspecific distance between its populations was from 0.3 to 9.8%.